Hippocampal Infolding Angle Changes during Brain Development Assessed by Prenatal MR Imaging - Righini, A. (AJNR Am J Neuroradiol, 2006)
BACKGROUND AND PURPOSE: Epileptic syndromes or neurodevelopmental delay may be associated with congenital anomalies of the shape or the orientation of the hippocampus. Scarce data are available about quantitative hippocampal developmental changes during fetal life, in particular about the progressive rotational changes of the hippocampal infolding angle (HIA), which can be considered a hallmark of hippocampal development. We hypothesized that prenatal MR imaging could demonstrate the progressive rotation of the hippocampus, providing quantitative data by means of the HIA determination. METHODS: We retrospectively selected 62 fetal MR imaging cases with normal brain at prenatal and postnatal imaging. The gestational age ranged from 20 to 37 weeks. The coronal section encompassing the pons was used to perform the measurement of HIA. HIA was defined as the angle between the line connecting the lateral margin of the cornu ammonis with the medial superior margin of the subiculum and the line passing through the midline structures. RESULTS: A significant positive correlation was found between the HIA value and the gestational age. The HIA was generally below 70° before the gestational week 25 and above 70° after week 30. CONCLUSION: Prenatal MR imaging allowed the progressive rotation of hippocampus to be detected during fetal life, providing normative data about HIA changes. These data could support further investigations to assess how fetal HIA anomalies might affect postnatal neurologic outcome.